2014 IEEE International Conference on Ultra-WideBand (ICUWB) 2014
DOI: 10.1109/icuwb.2014.6959020
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of UWB modulations over Nakagami-m fading channels with path-loss for an energy efficient railway balise application

Abstract: For the sake of developing an energy efficient railway balise, choosing an efficient energy modulation is very important. The main objective of this paper is to propose a complete analytical model to compare the energy efficiency of two well-known UWB modulations in Nakagami-m fading channel with path-loss. The results show that M-ary PPM is more efficient than M-ary PAM for high constellations, high communication ranges and high path-loss values. It also shows that, as we increase the number of receiver branc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 12 publications
0
0
0
Order By: Relevance
“…For the sake of simplification, a number of parameters of the IEEE 802.15.4a standard [10] is used and a Nakagami-m distribution for the radio propagation channel am-plitudes is adopted. This was integrated in the standard with the UWB path-loss model as described below.…”
Section: Channel Descriptionmentioning
confidence: 99%
See 2 more Smart Citations
“…For the sake of simplification, a number of parameters of the IEEE 802.15.4a standard [10] is used and a Nakagami-m distribution for the radio propagation channel am-plitudes is adopted. This was integrated in the standard with the UWB path-loss model as described below.…”
Section: Channel Descriptionmentioning
confidence: 99%
“…This algorithm is developed to search for energy efficient routes with respect to the Quality of Service (QoS) of the system. In [9] and [10] two well-known UWB modulations are compared, M-ary Pulse Position Modulation (MPPM) and M-ary Pulse Amplitude Modulation (MPAM), in the AWGN channel and the Nakagami-m fading channel respectively. The authors showed in both that the efficient technique has to be determined with respect to the transmission scenario and that generally MPPM is less energy consuming than MPAM for high constellations and long communication ranges.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation